Are instant payments becoming the new normal? A comparative study - Monika Hartmann; Lola Hernandez-van Gijsel; Mirjam Plooij; Quentin Vandeweyer (European Central Bank (ECB), 2019)
As a result of technological advancements, instant delivery of digital services has become the norm in today's society. Yet, until recently, this trend did not extend to retail payment services, which normally took one or up to a few working days from the end user's perspective. Following Europe's recent launch of its own SEPA-wide instant payment platform, now is the time to ask the question: will instant payment services become "the new normal" and what would this new normal look like? This paper assesses the overall prospects of instant payments in the euro area. It identifies structural drivers and blockers to the adoption of instant payments based on the analysis of country cases where instant payments became operational in the last few years.
Keywords: E41; E42; E58; 330; Instant payments; payment system; money demand